Numerical inspection based on Quasi-Static Analysis using Rousselier Damage Model for aluminium wingbox aircraft structure - Ahmad, Meor iqram Meor; Curiel-Sosa, J.L.; Akbar, Mahesa L.; Abdullah, Nur Azam (IOP Publishing Ltd, 2018)
The present paper illustrates a modelling technique of void damage prediction using constitutive Rousselier damage model in wingbox aircraft structure. The high possibility of aluminium wingbox structure to deform during operating become a driving force in this study. The Rousselier model is implemented by the user-defined material subroutine UMAT in the ABAQUS/ Standard. The wingbox is a part of a commercially-made commuter aircraft prototype, in which steady aerodynamic pressure is applied as the quasi-static, ranging from cruise load factor until the ultimate load factor. This analysis is divided into three assessments: load factor assessment, damage detection and implementation of Rousselier-UMAT-XFEM (RuX) model solution. The results indicate the maximum stress concentration occurs at the bottom-root part of the skin. The void volume fraction and the crack grow as the load factor increases to the ultimate load factor. A comparison with the literature is shown in some details.